The capacity and precision of visual short term memory - Murray, A; Alexandra M Murray (2012)
Despite continued interest in the capacity limitations of Visual Short-Term Memory (VSTM), there is uncertainty as to how these limited resources are distributed: among a limited number of high resolution slots or flexibly according to task demands. This thesis extends current knowledge by exploring how top-down and perceptual mechanisms affect VSTM capacity. The General Introduction describes the current understanding and investigation of capacity limits. This appraisal extends into Chapter 2, which focuses on the specific behavioural, psychometric, and electrophysiological approaches taken in this thesis to estimate effects on the precision and probability of recall of VSTM representations. Most experiments used a change-detection task that parametrically varied the precision of the VSTM representations required for accurate responses. Chapter 3 presents an event-related potential (ERP) study involving a pre-cue, which enabled a shift of spatial attention in anticipation of an upcoming memory array. ERP signatures of anticipatory spatial attention predicted behavioural cueing benefits. As a complement, the study in Chapter 4 involved orienting attention to items already in VSTM. Results from both chapters suggest that attention affects the probability of recall rather than the precision of representations. Chapter 5 describes four experiments exploring the ability to trade the number versus precision of representations in VSTM according to task goals. No flexibility was found in setting this trade-off, suggesting that the balance between number and precision is mainly determined by stimulus driven factors. Experiments in Chapter 6 investigate whether and how competitive dynamics that characterise perceptual processing continue to influence VSTM representations. Competition among item features that were orthogonal to the task relevant features continued to influence performance. Perceptual differences between the conditions cannot account for this effect. Competitive effects were consistent across spatial and non-spatial dimensions. The General Discussion synthesises all results and highlights opportunities for future research.